Teori Ragam Pengalaman Keagamaan William James: Sebuah Aplikasi terhadap Pengalaman Spiritual Pendiri Paguyuban Sumarah - Zakiy, Ahmad (YASIN, 2024)
There are several studies that examine the phenomenon of Paguyuban Sumarah beliefs. However, the various studies have only touched on issues such as motivation, influence, and the epistemology of the practice of the Sumarah mystical teachings. There is one aspect that is no less important and has not yet come to the attention of researchers, namely with regard to the spiritual experience by the founder of the teaching. This research aims to discuss Mr Sukino's spiritual experience using the religious experience approach of William James' perspective. The type of research used is field research using the descriptive-analytical analysis method. The result of this research is that there is a correspondence between William James' theory of religious experience and the spiritual experience experienced by Mr Sukino in affirming three things that become the validity of the experience, namely, direct understanding, philosophical validity and moral usefulness. The implications of research that uses William James' theory of religious experience to read a person's spiritual experience can make a benchmark for those who want to determine whether the religious experience really happened or is just an illusion.